The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3390/nano6080141
|View full text |Cite
|
Sign up to set email alerts
|

Galactosylated Liposomes for Targeted Co-Delivery of Doxorubicin/Vimentin siRNA to Hepatocellular Carcinoma

Abstract: The combination of therapeutic nucleic acids and chemotherapeutic drugs has shown great promise for cancer therapy. In this study, asialoglycoprotein receptors (ASGPR) targeting-ligand-based liposomes were tested to determine whether they can co-deliver vimentin siRNA and doxorubicin to hepatocellular carcinoma (HCC) selectively. To achieve this goal, we developed an ASGPR receptor targeted co-delivery system called gal-doxorubicin/vimentin siRNA liposome (Gal-DOX/siRNA-L). The Gal-DOX/siRNA-L was created via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 33 publications
1
30
0
1
Order By: Relevance
“…We found significantly higher accumulation of Cy3‐RΔF‐LA/miR NPs in the cytoplasm, indicating their efficient delivery and endosomal escape ability. The enhanced cellular uptake for the targeted NPs than the non‐targeted NPs in HCC cells was in agreement with earlier studies which have described the use of LA as the targeting ligand …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found significantly higher accumulation of Cy3‐RΔF‐LA/miR NPs in the cytoplasm, indicating their efficient delivery and endosomal escape ability. The enhanced cellular uptake for the targeted NPs than the non‐targeted NPs in HCC cells was in agreement with earlier studies which have described the use of LA as the targeting ligand …”
Section: Discussionsupporting
confidence: 92%
“…The enhanced cellular uptake for the targeted NPs than the nontargeted NPs in HCC cells was in agreement with earlier studies which have described the use of LA as the targeting ligand. (19,39,40) miRNAs have been shown to have profound effect on a wide variety of cellular processes including cell proliferation, migration and apoptosis. (6) Functional efficacy of RDF-LA/miR NPs in Huh7 cells with regard to these biological activities was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Simple PEGylated liposomes [51], advanced stimuli-responsive liposomes [52,53], and targeting liposomes [54,55] have all been constructed for siRNA/chemotherapeutic co-delivery in cancer. Using a PEGylated liposome to co-deliver, BCL2 siRNA with docetaxel successfully inhibited lung cancer in vitr o and in vivo [51].…”
Section: Liposomes or Lipid-based Nanoparticlesmentioning
confidence: 99%
“…Another study demonstrated the targeted co-delivery of siRNA and chemotherapeutic agent to liver tumors [54]. A liposomal carrier for the co-delivery of vimentin siRNA and doxorubicin was prepared from a mixture of lipids: DMKE (O,O’-dimyristyl-N-lysyl glutamate), cholesterol, galactosylated ceramide, POPC (1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine), and PEG2000-DSPE (distearoyl phosphatidyl ethanolamine).…”
Section: Liposomes or Lipid-based Nanoparticlesmentioning
confidence: 99%
“…Due to these characteristics, liposomes have previously been used as carriers of anticarcinogens (18)(19)(20). Galactosylated-liposomes, which specifically bind with the asialoglyco protein receptor (ASGPR) on the surface of liver cells are a type of liver targeting preparation (21). These liposomes may be transferred to liver cells via receptor-mediated endocytosis (RME) (22).…”
Section: Introductionmentioning
confidence: 99%